Anansi and the golden pot - Selasi, Taiye (DK, 2022)
"Kweku has grown up hearing stories about the mischievous spider Anansi. He is given the nickname Anansi by his father because of his similarly cheeky ways. On a holiday to visit his beloved Grandma in Ghana, Anansi the spider and Anansi the boy meet, and discover a magical pot that can be filled with whatever they want. Anansi fills it again and again with his favorite red-red stew, and eats so much that he feels sick. Will he learn to share this wonderful gift?"--